2014
DOI: 10.1371/journal.pone.0113803
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Ultrasound Facilitates the Exploration of Morphological Association of the Long Head Biceps Tendon with Supraspinatus Tendon Full Thickness Tear

Abstract: BackgroundsPathology of the long head biceps tendon (LHBT) is associated with rotator cuff tears but whether the LHBT texture changes following supraspinatus tendon full thickness tear (SSFT) can be detected at the extra-articular segment remains unknown. This cross-sectional study aimed to explore the morphological differences of the LHBT in shoulders with and without deficient rotator cuffs by using quantitative ultrasound.Materials and MethodsWe selected 145 cases with SSFT and 145 age-and- gender-matched c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 24 publications
(38 reference statements)
1
21
0
Order By: Relevance
“…4 Because the LHBT at the bicipital groove is the first structure scanned during a standard US imaging of the shoulder, BPE acts as an initial alerting sign for the rest of the examination. 5 Previous studies used a hypoechoic area of more than 2 to 3 mm around the LHBT as the diagnostic criterion for biceps tendinopathy or tenosynovitis. 6,7 The relationship between peritendinous effusion of more than 2 mm (as the diagnostic standard) and physical examination findings of LHBT lesions has been investigated.…”
mentioning
confidence: 99%
“…4 Because the LHBT at the bicipital groove is the first structure scanned during a standard US imaging of the shoulder, BPE acts as an initial alerting sign for the rest of the examination. 5 Previous studies used a hypoechoic area of more than 2 to 3 mm around the LHBT as the diagnostic criterion for biceps tendinopathy or tenosynovitis. 6,7 The relationship between peritendinous effusion of more than 2 mm (as the diagnostic standard) and physical examination findings of LHBT lesions has been investigated.…”
mentioning
confidence: 99%
“…The software Image J (National Institutes of Health, 9000 Rockville Pike, Bethesda, MD 20892) was used to conduct the measurements. Several previous researchers showed that using this method to quantify BPE, the correlation coefficients of inter- and intra-observer reliability can be up to 0.93 and 0.76, respectively891013. One previous study showed that effusion thickness more than 1 mm was associated with various sonographic pathologies of the shoulder10.…”
Section: Methodsmentioning
confidence: 98%
“…The supraspinatus tendon and subscapularis bursa were scanned by placing the arm behind the back to shift the tendon away from the coverage of the acromion. The hand was put on the contralateral shoulder during the examination of the infraspinatus tendon and the posterior shoulder recess891013. Regarding the dynamic subdeltoid imaging test; the arm was rested beside the trunk with the transducer placed lateral to the acromion along the scapular axis.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations